Troll Storms and Tort Liability for Speech Urging Action by Others: A First Amendment Analysis and an Initial Step Toward a Federal Rule - Clay Calvert (Washington University Law Review, 2020)
This Commentary examines when, consistent with First Amendment principles of free expression, speakers can be held tortiously responsible for the actions of others with whom they have no contractual or employer-employee relationship. It argues that recent lawsuits against Daily Stormer publisher Andrew Anglin for sparking “troll storms” provide a timely analytical springboard into the issue of vicarious tort liability. Furthermore, such liability is particularly problematic when a speaker’s message urging action does not fall into an unprotected category of expression, such as incitement or true threats, and thus, were it not for tort law, would be fully protected. In examining the possibility of vicarious tort liability, this Commentary reviews the U.S. Supreme Court’s “authorized, directed, or ratified” test for vicarious liability, which was established more than thirty-five years ago in the pre-Internet-era case of NAACP v. Claiborne Hardware Co. The Commentary concludes by proposing a framework for vicarious liability when speakers urge action that results in others’ tortious conduct.
Keywords: First amendment; Troll storm; Vicarious liability; Tort law; NAACP v. Claiborne Hardware Co 458 US 886; Free speech; Incitement